(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Persistent pneumonia in children pose a significant challenge to the pediatricians as there are underlying reasons of persistence. There are limited data on the underlying diseases predisposing to persistence of pneumonia in children. Objective: To identify the underlying diseases of persistent pneumonia in children. Methods: The cross sectional observational study was conducted at Bangladesh Shishu (Children) Hospital & Institute from November, 2019 to October, 2020. Children 2 months to 5 years of age admitted with persistent pneumonia were analyzed to find out the underlying diseases. Results: Among 49 cases of persistent pneumonia, underlying disease could be determined in 41 (83.7%) cases. The diseases were cystic fibrosis 13 (26.5%), congenital heart disease 10 (20.4%), primary immunodeficiency 10 (20.4%), gastro-esophageal reflux disease 5 (10.2%), pulmonary tuberculosis 4 (8.1%) and congenital anomalies of respiratory tract 1 (2%). Conclusion: The most common underlying diseases of persistent pneumonia are cystic fibrosis, congenital heart disease, primary immunodeficiency followed by gastro-esophageal reflux disease, pulmonary tuberculosis and congenital anomalies of respiratory tract. J Bangladesh Coll Phys Surg 2024; 42: 114-119